1991
DOI: 10.1111/j.1464-5491.1991.tb01566.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Haematocrit on Reagent Strip Tests for Glucose

Abstract: Four blood glucose reagent strips (BM-Test 1-44, Glucostix, Hypoguard GA, and Exactech), used in conjunction with measuring devices produced by the same manufacturer, were investigated with respect to the influence of haematocrit. The erythrocytes and plasma of fresh blood samples were separated, then remixed in different proportions to achieve a range of haematocrit values and the resulting specimens subjected to glucose assay. All the strip tests showed some influence of haematocrit, low haematocrits produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…13 It is theorized that with a high Hct, timed diffusion of glucose from blood onto the test strip is delayed as a result of the number of RBCs, which leads to spuriously low glucose values. Glucose concentrations in venous samples may underestimate those in arterial samples by 15%, and capillary samples also have lower blood glucose concentrations than do arterial samples.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is theorized that with a high Hct, timed diffusion of glucose from blood onto the test strip is delayed as a result of the number of RBCs, which leads to spuriously low glucose values. Glucose concentrations in venous samples may underestimate those in arterial samples by 15%, and capillary samples also have lower blood glucose concentrations than do arterial samples.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration of the glucometer and performance checks were carried out according to the manufacturer's instructions. Some glucose re¯ectance meters are sensitive to environmental factors and in particular the results obtained are altered by haematocrit 11,12 , pH 13 and pO 2 14 . However, the glucometer used in this study is not in¯u-enced by these variables.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that haematocrit may affect the results of blood glucose measurements with glucose meters (6,7). In this study both meters were affected by variations in haematocrit, showing an inverse relationship between glucose results and haematocrit values except for the Accutrend ® sensor at low blood glucose concentrations, where a slight opposite effect was seen ( Fig.…”
Section: Discussionmentioning
confidence: 50%